USE OF INTERACTIVE METHODS TRAINING IN PREPARING FUTURE TEACHERS FOR PEDAGOGICAL INTERACTION WITH STUDENTS (Pedagogy of Higher and Secondary Education, 2022)
In article the approaches to students' preparing to the pedagogical co-operation with pupils have been considered. Theeffectiveness of using interactive methods and ways of professionally significant features of future teachers forming process.